Liquid Smoke Fractionation from Dry Distillation of Styrofoam Board Waste to Produces Liquid Fuel - Anom, I Dewa K (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2021)
Styrofoam waste is difficult to be decomposed by bacteria or microorganisms. Therefore it takes a long time to be decomposed naturally. Styrofoam waste, in general, is a big problem for the survival of living things on earth because there are quite a lot of them. So, if not handled properly can cause environmental pollution. Styrofoam waste is inorganic waste composed of polymers derived from chemicals. Additives from styrofoam are harmful to humans because they are carcinogenic. This study aims to utilize Styrofoam board waste into liquid fuel. Liquid fuel from styrofoam waste has been made successfully through dry distillation and fractionation methods. The result of fractional distillation is 42.00% liquid fuel. Based on the physical properties tests that have already been carried out, including the density test, viscosity, flash point, boiling point, calorific value, and octane number, it turns out that the liquid has characteristics close to the standard gasoline fuel. The MS spectra and the GC chromatogram show that the liquid fuel consists of a mixture of hydrocarbon compounds, namely acetone 0.23%, acetic acid 0.40%, benzene 2.82%, toluene 3.56%, heptane 1.04%, 1-octene 0.26%, butyl ester 4.92%, 2,4-dimethyl-1-heptane 0.32%, p-xylene 13%, the compound with the highest composition was styrene 73.45%.